Antibacterial efficacy of in‐house designed cell‐penetrating peptide against multi‐drug resistant strains of Salmonella Enteritidis and Salmonella Typhimurium. (23rd September 2021) - Nishanth, Maria Anto Dani; Bhoomika, Sirsant; Gourkhede, Diksha; Dadimi, Bhargavi; Vergis, Jess; Malik, Satya Veer Singh; Barbuddhe, Sukhadeo Baliram; Rawool, Deepak Bhiwa
Summary: The in vitro antibacterial efficacy of an in‐house designed cell‐penetrating peptide (CPP) variant of Cecropin A (1–7)‐Melittin (CAMA) (CAMA‐CPP) against the characterized multi‐drug resistant (MDR) field strains of Salmonella Enteritidis and Salmonella Typhimurium were evaluated and compared with two identified CPPs namely, P7 and APP, keeping CAMA as control. Initially, the minimum inhibitory concentration (MIC) (μg ml −1 ) of in‐house designed CAMA‐CPP, APP and CAMA was determined to be 3.91, whereas that of P7 was 7.81; however, the minimum bactericidal concentration (MBC) of all the peptides were twice the MIC. CAMA‐CPP and CAMA were found to be stable under different conditions (high‐end temperatures, proteinase‐K, cationic salts, pH and serum) when compared to the other CPPs. Moreover, CAMA‐CPP exhibited negligible cytotoxicity in HEp‐2 and RAW 264.7 cell lines as well as haemolysis in the sheep and human erythrocytes with no adverse effects against the commensal gut lactobacilli. In vitro time‐kill assay revealed that the MBC levels of CAMA‐CPP and APP could eliminate the intracellular MDR‐ Salmonella infections from mammalian cell lines; however, CAMA and P7 peptides were ineffective. CAMA‐CPP appears to be a promising antimicrobial candidate and opens up further avenues for its in vivo clinical translation.